2014
DOI: 10.3389/fpsyg.2014.00311
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal multilevel CFA-MTMM model for interchangeable and structurally different methods

Abstract: One of the key interests in the social sciences is the investigation of change and stability of a given attribute. Although numerous models have been proposed in the past for analyzing longitudinal data including multilevel and/or latent variable modeling approaches, only few modeling approaches have been developed for studying the construct validity in longitudinal multitrait-multimethod (MTMM) measurement designs. The aim of the present study was to extend the spectrum of current longitudinal modeling approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 73 publications
(143 reference statements)
4
62
0
Order By: Relevance
“…While the former correspond with pure hierarchical data structures and meet the assumptions of the existing multilevel CFA-MTMM models proposed by Koch et al (2014) and Eid et al (2008), the latter correspond with crossed hierarchical data and violate the assumptions. Equation (5) shows how multilevel CFA-MTMM models can be modified to account for crossed random effects of targets and raters that arise from interchangeable methods with overlapping samples of raters.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…While the former correspond with pure hierarchical data structures and meet the assumptions of the existing multilevel CFA-MTMM models proposed by Koch et al (2014) and Eid et al (2008), the latter correspond with crossed hierarchical data and violate the assumptions. Equation (5) shows how multilevel CFA-MTMM models can be modified to account for crossed random effects of targets and raters that arise from interchangeable methods with overlapping samples of raters.…”
mentioning
confidence: 79%
“…Assuming that targets are rated on multiple indicators i , this problem has been resolved by the specification of a unidimensional measurement model for the rater effects UM trijkl across indicators, UMtrijkl=λUMijklUMtrjkl (see Eid et al, 2008, p. 233; Koch et al, 2014, p. 7). In Equation (3), UM trjkl reflects the random effect of rater r nested under target t which is considered constant across indicators i , and λ UM ijkl is the respective factor loading of indicator i 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Models for more complex MM designs. Koch, Schultze, Eid, and Geiser (2014) presented an extended CS-C(M -1) model for MM measurement designs that use both structurally different (fixed) and interchangeable (random) methods. A similar extension of Courvoisier et al's (2008) MM-LST model is discussed in Koch et al (in press).…”
Section: Outlook: Other Models For Mm-mo Datamentioning
confidence: 99%
“…There are many simulation studies and much analytic research on the performance of multilevel models. They have demonstrated that the required sample sizes strongly depend on model characteristics, mainly its complexity (Koch, Schultze, Eid, & Geiser, ; Meuleman & Billiet, ). Therefore, one cannot directly derive recommendations for the application of the model by Mahlke et al .…”
Section: Introductionmentioning
confidence: 99%